Synthesis, spectroscopic properties and photodynamic activity of a fulleropyrrolidine bearing a basic amino group and its dicationic analog against Staphylococcus aureus - Agazzi, Maximiliano Luis (2015)
N-Methyl-2-[4-(3-N,N-dimethylaminopropoxy)phenyl]fulleropyrrolidine (MPC60) was synthesized by 1,3-dipolar cycloaddition reaction of 4-(3-N,N-dimethylaminopropoxy)benzaldehyde, N-methylglycine and fullerene C60 in 43% yield. The amine groups of MPC60 were methylated with dimethyl sulfate to obtain a dicationic fullerene DPC602+ in 96 % yield. Absorption spectra of these fullerenes in N,N-dimethylformamide (DMF) and toluene/sodium bis(2-ethylhexyl) sulfosuccinate (AOT)/water reverse micelles showed strong absorptions in the UV region, with a peak at 430 nm and broader range of absorption up to 710 nm. Fluorescence quantum yields of about 10-4 were calculated for these compounds in DMF. A higher singlet molecular oxygen, O2(1Δg), generation was found for MPC60 than DPC602+ in DMF. The photodynamic activity of these photosensitizers remained high in a simple biomimetic AOT system. Also, the formation of superoxide anion radical induced by MPC60 and DPC602+ was detected in presence of NADH. Decomposition of l-tryptophan in DMF mediated by both fullerenes indicated a possible contribution of type I photoprocess. Photosensitized inactivation of Staphylococcus aureus was investigated using different conditions. Cell suspensions of 108 cells/mL incubated with 0.5 μM fullerene and irradiated for 30 min exhibited a 4.4 and 5.0 log decrease of cell survival by MPC60 and DPC602+, respectively. Therefore, these fullerene derivatives can be used as effective photosensitizers for the photodynamic inactivation of S. aureus cells.